Lewis Base Catalyzed Asymmetric Hydrosilylation of α-Substituted β-Enamino Esters: Facile Access to Enantioenriched β2-Amino Esters via Dynamic Kinetic Resolution - Shu, Chang; Hu, Xiao-Yan; Li, Shuai-Shuai; Yuan, Wei-Cheng; Zhang, Xiao-Mei (Synlett, 2014)
A chiral Lewis base organocatalyzed asymmetric hydrosilylation of α-substituted β-enamino esters is presented. The reactions proceeded through dynamic kinetic resolution to afford various enantioenriched β2-amino esters with high yields (up to 98%) in moderate enantioselectivities (up to 77% ee).
Keywords: asymmetric catalysis; dynamic kinetic resolution; β2-amino acids; hydrosilylation; Lewis base